Healthcare workers' beliefs, attitudes and compliance with mobile phone hygiene in a main operating theatre complex. Issue 1 (March 2020) - Leong, Xin Yu Adeline; Chong, Shin Yuet; Koh, Si En Angel; Yeo, Bee Chin; Tan, Kwee Yuen; Ling, Moi Lin
Summary: Background: Phone hygiene is increasingly recognized in infection prevention. We aimed to explore the beliefs, attitudes and performance of phone hygiene amongst healthcare workers (HCWs) in the major operation theatre (MOT) complex of a Singapore tertiary acute care hospital. We also monitored the impact of phone hygiene stations, introduced to improve phone hygiene. Methods: We sent two online anonymous surveys to the Departments of Anaesthesia and MOT Nurses one month before and after we set up phone hygiene stations. Four phone hygiene stations displaying visual phone hygiene reminders and Mikrozid® sensitive wipes were set up at MOT entrances. Results: A total of 205 and 91 HCWs responded to the first and second surveys respectively. In the first survey, 11.5% cleaned their phones daily while 9.4% never cleaned their phones. These changed to 16.9% and 3.8% respectively after the introduction of phone hygiene stations. 80.0% in the first survey said they would clean their phones more often if there were a readily accessible disinfection method in the MOT. A majority believed phones are a source of healthcare associated infection. Common reasons for not cleaning phones were 'lack of available resources' and 'I don't think about it.' Senior doctors were the least compliant to phone hygiene. Conclusion: Phone hygiene is easily overlooked during our busy workday. Besides increasing awareness of phone hygiene, having a readily available disinfection method in the MOT complex is important to improve phone hygiene. We suggest HCWs clean their phones before entering and/or after leaving the MOT daily.